3.1. Zapisz podany wzór funkcji kwadratowej f w postaci ogólnej f(x) = a * x ^ 2 + bx + c . Następnie wypisz współczynniki a, b, c. a) f(x) = (x – 1)(2x + 3) – 4x c) f(x) = – 3[(x – 2)(2x + 3) + 6] b) f(x) = 5 – 2 * (x + 4) ^ 2 d) f(x) = (1 – 2x) ^ 2 + 4(x – 1) + 3

3.1. Zapisz podany wzór funkcji kwadratowej f w postaci ogólnej f(x) = a * x ^ 2 + bx + c . Następnie wypisz współczynniki a, b, c. a) f(x) = (x – 1)(2x + 3) – 4x c) f(x) = – 3[(x – 2)(2x + 3) + 6] b) f(x) = 5 – 2 * (x + 4) ^ 2 d) f(x) = (1 – 2x) ^ 2 + 4(x – 1) + 3